A Study of Fall from Height Accidents in High-rise Building Construction Sites in Selangor - Lee, Benny Hai Chim; Liaw, Zhi Ying; Kong, Sio Kah (INTI International University, 2019)
The construction industry is a high-risk industry which is proned to cause accidents resulting in fatalities and injuries compared to other industries. Fall from height is one of the most critical accidents that occurs frequently on high-rise project sites.There is a far reaching implication on the time, cost and quality of the project when safety is neglected on site. Henceforth, this research is presented with the aim of investigating the occurrence of fall from height accidents in the high-rise building construction sites.In order to achieve the aim of this research, data were collected through online distribution of structured questionnaires to safety officers in Selangor area. Frequency distribution analysis, mean score analysis and T-test analysis are employed to analyse the findings of this research.The outcomes of this study enlighten the stakeholders on the site safety knowledge so that effective actions can be implemented to prevent fall from height accident from occurring in high rise building construction sites.